Environmental awareness and leadership commitment as determinants of IT professionals engagement in Green IT practices for environmental performance - Ojo, Adedapo Oluwaseyi; Muhammad Ashraf, Fauzi (Elsevier Ltd, 2020)
Green IT (GIT) has become essential in ensuring the sustainable consumption and production of IT equipment for positive environmental outcomes. Nevertheless, existing studies on GIT practices have focused on the organizational level, with limited emphasis on the engagement of the IT professionals in sustainable environmental performance. Thus, the present study draws on the belief action and outcome (BAO) framework to investigate the factors of IT professionals' GIT beliefs and attitudes toward adopting GIT practices for environmental performance. The hypothesized model was tested with data collected from 333 IT professionals in Malaysia. The results of path analysis supported the significant impacts of environmental awareness and leadership commitment in shaping IT professionals' GIT beliefs and attitudes. Also, their attitude was a significant mediator between beliefs and engagement in GIT practices, and both GIT attitudes and practices were significantly related to environmental IT performance. This study offers empirical support for the role of IT professionals in enhancing environmental performance through engagement in sustainable IT practices.